Microfinancing as a tool for poverty alleviation - Alcantara, Jaime; Alcantara, Jaime; Baluya, Roxanne; Escobar, Marla; Lacson, Elgin
Microfinancing has been widely applied in the Philippines especially in the rural areas. The evolution of the model has been summarized in this study other and studies were conducted to assess the impact of the microfinancing model applied by Lifebank in Sta. Barbara, Iloilo. The results indicate that the program The results indicate that the program has reached the poor and has benefited positively in terms of income, consumption and nutrition, and the empowerment of women as able providers. Suggestions have been made for a more thorough assessment of the impact of the program by Lifebank and additional research was conducted to find out whether the common notion that microfinancing is indeed a tool for poverty alleviation or not.
[Research Paper] (Mgt 299). -- [Iloilo City : UPV-CM, n.d.]